Creating a Roadmap Towards Circularity in the Built Environment - Bragança, Luís; Cvetkovska, Meri; Askar, Rand; Ungureanu, Viorel (Springer Tracts in Civil Engineering,, 2024)
This open access book summarizes the research being pursued as part of the COST Action CA21103 titled "Implementation of Circular Economy in the Built Environment" (Circular B), which aims to define the methodology to develop a common circularity framework for inclusive application and assessment in new and existing buildings to support decision-making for all value chain stakeholders and appraise the implementation level of the European Circular Economy Action Plan (CEAP). The Action is increasingly gaining interest worldwide, bringing multidisciplinary young and experienced researchers together to share the latest studies and develop new knowledge. Consisting of 17 chapters corresponding to the conference themes, the book analyses and discusses topics such as Circular Economy (CE) best practices, design strategies for circular buildings, circular materials and products, adaptive reuse of existing buildings, recovery and reuse of salvaged materials and products, case studies of current applications and trends, barriers against CE implementation in buildings, efficient waste and circular resource management, circular lifecycle management and decision making, stakeholders relationships, CE supporting policies and barriers, circular business models, criteria, KPIs and assessment models for circular buildings, CE criteria in sustainability frameworks, digitalization and BIM for enhanced circularity of buildings and building materials, and standardization of CE definitions in buildings.